(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
Let \(G=(V,E)\) be a graph with vertex set \(V\) and edge set \(E\). Consider a vertex labeling \(f:V(G)→ {0,1,2}\) such that each edge \(uv\) assign the label \((f(u)+f(v)) ({mod 3)\). The map \(f\) is called a 3-total sum cordial labeling if \(|f(i)-f(j)|1\), for \(i,j {0,1,2}\) where \(f(x)\) denotes the total number of vertices and edges labeled with \(x={0,1,2}\). Any graph which satisfied 3-total sum cordial labeling is called a 3-total sum cordial graph. Here we prove some graphs like wheel, globe and a graph obtained by switching and duplication of arbitrary vertex of a cycle are 3-total sum cordial graphs.